EXPLORING THE INFLUENCE OF TAXATION ON NIGERIA’S ECONOMIC GROWTH: AN IN-DEPTH ANALYSIS (AUN INTERNATIONAL CONFERENCE, 2024)
This study examined the impact of taxation on economic growth in Nigeria for the period 2003 to 2023. The study was based on the ex-post facto research design and the expediency theory of taxation. To achieve the study objective data were gathered on Gross Domestic Product (GDP) as dependent variable and components of taxation in Nigeria including Companies Income Tax Revenue (CIT), Customs Duties Revenue (CUD), Value Added Tax Revenue (VAT), and Petroleum Profit Tax Revenue (PPT). The study conducted both the pre-estimation and post estimation tests for the variable’s trending, unit root, cointegration, causality, normality and stability. Furthermore, an ARDL model was used to determine the variable’s parameters and p-statistics test was employed to examine their significance. The results obtained shows that Company income tax (CIT) has an insignificant negative impact on economic growth such that a unit change in CIT, tend to decrease GDP by N30914.88 billion; Custom duty (CUD) has a significant negative impact on economic growth such as a unit change in CUDR, tend to decrease GDP by N340888.2billion; Value added tax (VAT) has a significant positive impact on economic growth such that a unit change in VATR, tend to increase GDP by N483495.3 billion; and Petroleum profit tax (PPT) has an insignificant negative impact on economic growth such that a unit change in PPTR, tend to decrease GDP by N19280.79 billion. The study recommends among others that the Nigerian government should reform the company income tax system to make it more efficient and less burdensome on businesses, particularly small and medium-sized enterprises (SMEs). This could include reducing the tax rate, streamlining the tax filing process, and providing tax incentives for businesses that invest in research and development, innovation, and job creation.